Unknown Pieces for Classical Guitar by Juan José Mantecón and Jesús Bal y Gay, Two Galician Musicians of the Generation of 27 - Diz, Samuel (Madrygal. Revista de Estudios Gallegos, 2015)
Atardecer and Pastoral are two unknown musical pieces for classical guitar by Galician composers Juan José Mantecón (1895-1964) and Jesús Bal y Gay (1905-1993), dedicated to guitarist Regino Sainz de la Maza (1896-1982), and recovered recently in the project Galician classical guitar by musician and researcher Samuel Diz (Tui, 1986) and the publisher Ouvirmos.